A Literature Review on Operations Management and Strategy - Malik, Yaumil Fauzan; Ernawati, Dyah Poespita; Rizkiyanti, Amanda Aurelia (Universitas Pendidikan Ganesha, 2024)
This paper distinguishes between operations management and operations strategy, both of which play crucial roles in achieving organizational success. Operations management focuses on the efficient management of production processes, from input acquisition to output delivery, ensuring high-quality products and services. It involves key aspects like inventory control, capacity planning, quality management, and cost reduction. Over time, it has evolved with technological advancements and new methodologies like Just-In-Time (JIT) and Total Quality Management (TQM), emphasizing continuous improvement to meet customer expectations. On the other hand, operations strategy is concerned with aligning operational resources and capabilities with long-term market demands and business objectives. It involves strategic decision-making, such as competitive positioning, resource allocation, and innovation, and plays a vital role in shaping a company’s growth and sustainability in the marketplace. While these two areas are closely related, operations management typically addresses short-term operational tasks, whereas operations strategy focuses on long-term goals. This paper explores the differences and interconnections between operations management and strategy, integrating expert opinions and discussing their practical implications in both private and public sectors. Case studies, such as Tesla's operations strategy and Australia's Net Zero Plan 2050, illustrate how effective operations management and strategy drive both innovation and competitive advantage in dynamic markets.